Peran Islamic Social Finance Filantropi dalam Pengentasan Kemiskinan di Kabupaten Karanganyar - Wahyudi, Agung; Fauzi, Achmad Noor; Suranto (Nur Science Institute, 2023)
This study aims to determine the role of Islamic social finance in alleviating poverty in Karanganyar Regency, Central Java. Therefore this research uses a descriptive qualitative approach, then the subject of this research is Baznaz Karanganyar Regency, data collection techniques in this study are in the form of interviews, observation, documentation, analysis. The results of this study show that the overall performance of Baznaz Karanganyar Regency is very good in terms of work programs, zakat reception strategies, distribution of zakat infaq alms, zakat collection units and zakat collection officers. The contribution of Islamic social finance to this district baznaz philanthropic institution has been real and can be done concretely in one of the solution efforts, namely overcoming poverty alleviation. For its success and being a role model, in 2022 Baznaz Karanganyar Regency received appreciation from Bank Indonesia in Central Java as the best amil zakat institution supporting the sharia economy in the Central Java region.